Evaluating the attitude of students and operating room staff about teamwork and its related factors - Ali Asghar Ghods; Seifollah Alaei; Fateme Abdollahi; Masomeh Assarhossainy (Payesh, 2025)
Objective (s): Understanding structure, attitude of team members, interactions and factors affecting on teamwork, is important to enhance quality of surgery. Therefore, this study was conducted aiming to evaluate teamwork attitude in students and operating room staffs in anesthesia and operation rooms. Methods: This cross-sectional study was conducted from November 2022 to May 2023 on 260 members, including operating room staffs of a teaching hospital, students of the operating room and anesthesia in paramedic faculty of Semnan University of Medical Sciences. Evaluation of the attitude regarding teamwork was done through a self-designed teamwork attitude questionnaire. After providing preliminary explanations and obtaining informed consent, the questionnaire was given participants and collected after completion and analyzed with appropriate statistical tests. Results: Overall teamwork attitude score was 59.95±12.84 and showed somewhat above average. According to the findings, there was a significant relationship between age and teamwork attitude (P=0.007), but there was no significant relationship between years of work/education and teamwork attitude (P=0.91). Conclusion: The attitude of students and staff of the operating room regarding teamwork was somewhat higher than the average level. Appropriate solutions should be thought to increase the motivation and tendency of operating room staffs toward teamwork issue.